Pengembangan Dokumentasi Penskoran Early Warning System sebagai Deteksi Dini Penurunan Kondisi Pasien - Nelly Hermala Dewi; Enie Novieastari; Lisnawati Yupartini (Universitas Faletehan, 2023)
The implementation of a scoring warning system by nurses can determine patient safety. Early warning system (EWS) is a tool to detect patient emergencies by scoring on seven parameters. The purpose of this study was to determine the development of early warning system (EWS) documentation, the quality of format development, and the quality of format development documentation. The research method was research and development. The study was carried out in adult inpatient wards and the sample size was 62 nurses. The data collection tools were questionnaires and observation sheets. The analysis used univariate with frequency distribution. The result of this research was the development of early warning system documentation, including the parameters of mean arterial pressure (MAP), blood glucose, pain scale, and urine output. The quality of EWS documentation format development was well-functioned, efficient, and usable. In addition, the quality of EWS documentation, including completeness, accuracy, relevance, and good novelty, was in a good category. The conclusion was that the development of early warning system documentation can be used in adult inpatient wards to improve patient safety practices